Calyptocarpus (Asteraceae: Heliantheae: Ecliptinae), a newly naturalized genus in Tropical East Africa - Shen, Jia-Hao; Hu, Guang-Wan; Gao, Tian-Gang (Phytotaxa, 2020)
Calyptocarpus, a newly naturalized genus of Asteraceae was recorded in tropical east Africa based on morphology and molecular evidence. It is similar to Synedrella but different by its non-winged ray achenes and acute paleae apex. Calyptocarpus vialis, the only species of this genus recorded in Africa, is described and illustrated. A key to the genera of the subtribe Ecliptinae in tropical east Africa is also presented.